Rock monuments in the collection of the National Museum of Tuva - Mongush, Chechena A.-S. (The New Research of Tuva, 2019)
The Aldan Maadyr National Museum of the Republic of Tuva has more than 160 rock monuments of various periods in its collection. They have largely been found in central, eastern and southern rayons of Tuva. Stones and steles from Tuva can also be seen in a number of museums across Russia and abroad. The article provides a description of the collection, including its most interesting pieces, photos, inscription samples (with translation). We also focus on acquisition dates and contributions made by researchers.The collection can be categorized into seven chronological groups: stones with animal imagery (Bronze Age, late 3rd millennium BCE - 9th century BCE); Scythian deer stones (9th -3rd centuries BCE); Old Turkic stone anthropomorphic figures (6th - 8th centuries CE); Old Uighur stone sculptures (8th -9th centuries CE); stelae with runic inscriptions in Old Turkic (9th -12th centuries CE); rock monuments of the heyday of the Mongolian empire (early 13th – late 14th centuries CE); and the stone slabs with inscriptions in Tibetan and Sanskrit (late 19th – early 20th centuries CE). Of all rock monuments, 93 are permanently featured in the museum’s exposition, and the rest are preserved in special collections.
Keywords: runic writing; monuments of Old Turkic runic writing; National Museum of the Republic of Tuva; Old Turkic culture